INFLUENCE OF WHEEL POLYGON ON DYNAMIC PERFORMANCE OF HIGH SPEED EMU - ZHANG JieJuan; SHANG YueJin; WANG Hong; XUE Hai; LI ZhenHua; YANG PengPeng (Jixie qiangdu)
With the continuous improvement of the running speed of the EMU,the wear of the wheels during the operation is intensified,which increases the maintenance cost and deteriorates the service environment of the train. In severe cases,it will threaten the safety of driving. Aiming at the polygon problem caused by wheel running wear,the dynamic high-speed EMU of a certain type of line is taken as the research object. The dynamic model was established by SIMPACK,and analyzed the influence of wheel polygon（ polygon number 1 ～ 11,wheel polygon amplitude 0. 1 mm ～ 0. 5 mm） on the vertical vibration response of high-speed wheel-rail system. In order to visually observe the relevant changes,a coefficient of decision was introduced and the curve is fitted to its variation. The results show that the influence of the wave depth of the wheel polygon on the vertical vibration response is more significant. The obtained fitting curve provides reference for the detection and maintenance and safety assessment of the high-speed EMU.